2022
DOI: 10.1021/acs.est.2c04652
|View full text |Cite
|
Sign up to set email alerts
|

Discharge of Polyphosphonate-Based Antiscalants via Desalination Brine: Impact on Seabed Nutrient Flux and Microbial Activity

Abstract: Desalination brine is a hypersaline byproduct that contains various operational chemicals such as polyphosphonate-based antiscalants. Brine often sinks and flows over the seabed by density currents; therefore, it may affect sediment-water nutrient fluxes and thus microbial activity. We quantified these parameters in brine plumes around two large-scale desalination facilities located in the P-limited Southeastern Mediterranean Sea. The benthic nutrient fluxes and microbial activity were determined using ex-situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…It should be noted that the density differences between the diluted brine and the ambient seawater required to support the formation and propagation of gravimetric density currents are quite small . The above-mentioned study argued that the far-field propagation (<13 km 2 ) of desalination brines will form a higher density layer above the seabed that can impede the vertical mass transfer of nutrients from the sea bottom to the overlying water, , similarly to reports from the mixing zone …”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…It should be noted that the density differences between the diluted brine and the ambient seawater required to support the formation and propagation of gravimetric density currents are quite small . The above-mentioned study argued that the far-field propagation (<13 km 2 ) of desalination brines will form a higher density layer above the seabed that can impede the vertical mass transfer of nutrients from the sea bottom to the overlying water, , similarly to reports from the mixing zone …”
Section: Resultsmentioning
confidence: 83%
“…Polyphosphonate-based antiscalants are not considered to be a form of phosphorus used by organisms. However, a recent study that sampled sediment and porewater from the discharge area of a large-scale desalination facility indicated that these antiscalants can be degraded, leading to the release (∼40x higher than the intake water) of dissolved organic phosphate, DOP . This additional load of organic phosphate has been shown to enhance bacterial metabolism at the diffusive boundary layer .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Hence, phosphonates could be a potential source of bioavailable P. Indeed, Sisma-Ventura et al found that the discharge of polyphosphonate-containing desalination brine to coast areas stimulated microbial activity in the seabed. 19 Hasanin et al also reported that phosphonates significantly promote bacterial growth under phosphorus-limiting conditions, thus leading to membrane fouling when used as antiscalants. 20 Moreover, phosphonate compounds also exhibit toxicity to aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to note that phosphonates cannot be mineralized in WWTPs . Along with their widespread application yet poor degradation in WWTPs, phosphonates are frequently detected in sewage sludge, effluents of WWTPs, lakes, rivers, and oceans. In water bodies, phosphonates can be slowly converted to phosphate through enzymatic or photochemical reactions. , Hence, phosphonates could be a potential source of bioavailable P. Indeed, Sisma-Ventura et al found that the discharge of polyphosphonate-containing desalination brine to coast areas stimulated microbial activity in the seabed . Hasanin et al also reported that phosphonates significantly promote bacterial growth under phosphorus-limiting conditions, thus leading to membrane fouling when used as antiscalants .…”
Section: Introductionmentioning
confidence: 99%